FACTORS AFFECTING FIRM VALUES WITH GOOD CORPORATE GOVERNANCE AS MODERATING VARIABLES IN MANUFACTURING MANUFACTURERS OF CONSUMPTION GOODS SECTORS LISTED IN INDONESIA STOCK EXCHANGE - Nasution, Gunung (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to examine and analyse the effect of leverage, profitability, dividend payout ratio (DPR) and free cash flow (FCF) on firm value with good corporate governance (GCG) as a moderating variable. The population in this study were 37 consumer goods manufacturing companies listed on the Indonesia Stock Exchange in the period of 2015-2017, with a purposive sampling technique so that 34 samples were collected. The data analysis method uses multiple linear regression analysis and interaction testing with the help of the Eviews application program. The results showed that the profitability and dividend payout ratio (DPR) partially had a positive and significant effect on firm value, while leverage and free cash flow (FCF) partially had a positive and not significant effect on firm value. Simultaneously leverage, profitability, dividend payout ratio (DPR) and free cash flow (FCF) affect the value of the company. Good Corporate Governance (GCG) as a moderating variable is not significant in partially moderating influence of leverage, profitability, dividend payout ratio (DPR) and free cash flow (FCF) on the value of the company in companies manufacturing consumer goods sector listed on the Indonesia Stock Exchange period 2015-2017.